Discrete element modeling and parameter calibration of safflower biomechanical properties - Zhang, Zhenguo; Zeng, Chao; Xing, Zhenyu; Xu, Peng; Guo, Quanfeng; Shi, Ruimeng; Wang, Yunze (International Journal of Agricultural and Biological Engineering, 2024)
Understanding the biomechanical properties of safflowers is essential for appropriately designing harvestingmachinery and optimizing the harvesting process. Safflower is a flexible crop that lacks a basis for relevant simulationparameters, which causes difficulties in designing harvesting machinery. In this study, a calibration method for safflowers wasproposed. First, a discrete element model was established by measuring the intrinsic parameters of a safflower, such as itsgeometric parameters, density, Poisson’s ratio, and modulus of elasticity. Second, the contact and bonding parameters werecalibrated using a combination of physical and simulation tests. In the contact parameter tests, the Hertz-Mindlin (no-slip)model was implemented for the stacking angle tests conducted regarding the safflower filament. A regular two-level factorialdesign was used to determine the important factors and perform the steepest climb test. Moreover, the Box-Behnken design wasadopted to obtain the optimal contact parameters. In the bonding parameter tests, the Hertz-Mindlin model with bonding contactwas applied for the safflower shear simulation tests; moreover, the optimum bonding parameters were obtained through thecentral composite design test. The results demonstrated that the relative errors between the simulated and measured stackingangles and maximum shear were 3.19% and 5.29%, respectively. As a result, the safflower simulation parameters wereaccurately calibrated, providing a reference for appropriately setting the simulation parameters and designing key mechanicalcomponents. Keywords: safflower, DEM, parameter calibration, shear test, biomechanical properties DOI: 10.25165/j.ijabe.20241702.8857 Citation: Zhang Z G, Zeng C, Xing Z Y, Xu P, Guo Q F, Shi R M, et al. Discrete element modeling and parameter calibrationof safflower biomechanical properties. Int J Agric & Biol Eng, 2024; 17(2): 37–46.